Dynamic Parameter Design Method and Application under a General Linear Relationship between Response Variables and Signal Factors. Issue 4 (March 2020) - Yu, Lanting; Zhang, Yueyi; Zhu, Hong; Mao, Ting
Abstract: In dynamic parameter design, there is often a different functional relationship between response variables and signal factors. SNR is an important tool for the parameter design of dynamic characteristics, and its estimation results change with the change of function relationships. This paper describes the dynamic parameter design method in a linear relationship between response variables and signal factors, and provides a case for verification. The results of this study are applicable to engineers and academics who need to conduct product design, process development and process optimization through dynamic parameter design.